Designing an E-learning Environment for Self-directed Japanese Language Learners - Shinohara, Misaki (KIRYOKU, 2025)
This study aims to design an e-learning environment to support autonomous learning in Japanese language education and to explore its applicability.  In recent years, as the need for an educational environment that promotes learners’ independent learning has increased, support methods using ICT have been attracting attention.  As part of this study, an online learning portal was designed for Indonesian university students.  The platform incorporates self-assessment tools, progress management functions, and interactive learning materials.  Results showed that over 90% of learners reported increased motivation and a greater sense of self-regulation.  Learners were observed to exhibit autonomous learning behaviors, such as selecting learning materials that suited their needs and actively reviewing and gathering information outside of class.  On the other hand, some learners who were accustomed to the traditional sentence-based learning method had difficulty adapting to the new approach.  As a result, it was shown that a structured and flexible e-learning design with self-assessment functions and progress confirmation tools is effective in supporting autonomous learning.   This study suggests that a technology-based learning environment may contribute to improving learning motivation and autonomy in the context of Japanese language learning.